Geosynthetic reinforced walls with clayey fills - Choa, Victor. (2008)
The main objective of this project is to investigate the behaviour of geosynthetic reinforced wall with clay backfill (GRWC), under various conditions. The wall behaviour under as-compacted and soaked condition was investigated.